Female Attorneys in South Africa: A Quantitative Analysis - Meyer, Tamlynne (African Journal of Employee Relations, 2019)
Law is an established profession, traditionally white, male and middle-class. Since 1994, there has been a strong focus on transformation in the South African legal profession, largely focusing on racial transformation, with meaningful gender transformation lagging behind. This article illustrates at a quantitative level the gendered landscape of the South African attorney’s profession. The findings show that in the past decade there has been a steady increase in the number of female law graduates and the number of females admitted as attorneys. The occupational structure shows that the junior levels of the profession are dominated by females, and that there is a lack of diversity and transformation as regards the senior and most sought-after positions in the profession. Not only are female partners outnumbered, they are also significantly under-represented, with only half of them being represented at the partnership level, whereas males are over-represented at that level. South Africa has no shortage of laws and policies promoting gender equality and transformation. Unfortunately, these laws and policies have done very little to liberate female attorneys as they move through the ranks of the profession. The article concludes by raising questions that should be qualitatively explored in future research.